Effective concepts of management against the challenges of the modern world: Lean and Agile: competition or cooperation? - Milewski, Dariusz; Milewska, Beata (Ekonomia i Prawo. Economics and Law, 2024)
Motivation: For a long time, new strategies, concepts and solutions regarding both process management in enterprises and managing the supply chains have been presented in the literature and implemented in business practice. They are to be an alternative to existing concepts. Considerations regarding these concepts focus on the speed of adaptation to changing conditions in the environment, flexibility, diversification and reducing the risk of disruption. The justification for the implementation of new solutions are the conditions and challenges in the environment of enterprises, especially the Covid-19 pandemic, but also economic crises, wars, terrorism, natural disasters, changes in energy prices. An example of such a concept is the Agile strategy. According to some authors, this strategy is a competitive concept to Lean Management. Other authors believe that they are complementary and that there are opportunities to combine them and thus achieve a synergy effect. Aim: The aim of the article is to compare the effectiveness of Lean and Agile process and supply chain management strategies in conditions of environmental instability, based on literature review and own research. Results: Lean and Agile strategies can be combined to some extent. In addition, such a combination may prove to be more effective and more resistant to interference than using “clean” strategies. The result of proper application of both strategies are lower costs, better product quality, higher level of logistics service, greater customer satisfaction and employee involvement, and thus the trade-up effect.